Breaking the mold: 3D cell cultures reshaping the future of cancer research - Cordeiro, Sandra; Oliveira, Beatriz B.; Valente, Ruben; Ferreira, Daniela; Luz, André; Baptista, Pedro V.; Fernandes, Alexandra R. (Frontiers in Cell and Developmental Biology, 2024)
Despite extensive efforts to unravel tumor behavior and develop anticancer therapies, most treatments fail when advanced to clinical trials. The main challenge in cancer research has been the absence of predictive cancer models, accurately mimicking the tumoral processes and response to treatments. The tumor microenvironment (TME) shows several human-specific physical and chemical properties, which cannot be fully recapitulated by the conventional 2D cell cultures or the in vivo animal models. These limitations have driven the development of novel in vitro cancer models, that get one step closer to the typical features of in vivo systems while showing better species relevance. This review introduces the main considerations required for developing and exploiting tumor spheroids and organoids as cancer models. We also detailed their applications in drug screening and personalized medicine. Further, we show the transition of these models into novel microfluidic platforms, for improved control over physiological parameters and high-throughput screening. 3D culture models have provided key insights into tumor biology, more closely resembling the in vivo TME and tumor characteristics, while enabling the development of more reliable and precise anticancer therapies.